PENERAPAN METODE WEIGHTED MOVING AVERAGE DALAM MEMPREDIKSI PENGELUARAN BARANG BERBASIS WEB DI TOKOODISE RAWABUNTU - Iswanto (Jurnal Penelitian Ilmu komputer, 2023)
Tokoodise is a printing company that focuses on selling artwork images to be used as wall murals and wall decals for housing or offices, with sales increasing from year to year. The large number of various types of materials that Tokoodise sells, owners often have difficulty estimating future inventory and expenditure of goods based on previous recorded data, this is very influential in determining the amount of goods that must be provided. So that in the problems above the author uses forecasting methods to predict the expenditure of goods which is expected to be a support for decisions in the inventory of goods that must be prepared in the future. One type of time series method in forecasting is the method Weighted Moving Average (WMA), namely a method that gives different weights to each historical past for each available historical data in the past, with the assumption that the most recent or recent historical data will have greater weight compared to old historical data, because the most recent data or newest data is the most suitable for forecasting.